The Glutathione Metabolite γ-Glutamyl-Glutamate Partially Activates Glutamate NMDA Receptors in Central Neurons With Higher Efficacy for GluN2B-Containing Receptors - Sebih, Fatiha; Mokrane, Nawfel; Fontanel, Pierre; Kayatekin, Mete; Kaabeche, Mahira; Guiramand, Janique; Cohen-Solal, Catherine; Cens, Thierry; Rousset, Matthieu; Charnet, Pierre; De Jésus Ferreira, Marie-Céleste; Thibaud, Jean-Baptiste; et al. (Frontiers in Pharmacology, 2022)
Gamma-L-glutamyl-L-glutamate (γ-Glu-Glu) was synthetized and further characterized for its activity on cultured neurons. We observed that γ-Glu-Glu elicited excitatory effects on neurons likely by activating mainly the N-methyl-D-aspartate (NMDA) receptors. These effects were dependent on the integrity of synaptic transmission as they were blocked by tetrodotoxin (TTX). We next evaluated its activity on NMDA receptors by testing it on cells expressing these receptors. We observed that γ-Glu-Glu partially activated NMDA receptors and exhibited better efficacy for NMDA receptors containing the GluN2B subunit. Moreover, at low concentration, γ-Glu-Glu potentiated the responses of glutamate on NMDA receptors. Finally, the endogenous production of γ-Glu-Glu was measured by LC-MS on the extracellular medium of C6 rat astroglioma cells. We found that extracellular γ-Glu-Glu concentration was, to some extent, directly linked to GSH metabolism as γ-Glu-Glu can be a by-product of glutathione (GSH) breakdown after γ-glutamyl transferase action. Therefore, γ-Glu-Glu could exert excitatory effects by activating neuronal NMDA receptors when GSH production is enhanced.